(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This study aims to determine influence of charismatic leadership, motivation, and organizational culture on the performance of KPP Pratama Wonosari employees with job satisfaction serves as moderating variable. The method used in this research is quantitative method, where data collection uses questionnaires. The sample in this study amounted to 68 employees, where these employees served in KPP Pratama Wonosari. Validity test which shows that the statement in this study is valid, while the reliability test using Cronbach Alpha is declared reliable. This research uses SEM-SmartPLS analysis. The results of this analysis show that charismatic leadership, motivation, and job satisfaction has positive and significant effect on employee performance. Meanwhile, organizational culture do not serve any significant effect on employee performance. Moderating variable (job satisfaction) shows that it strenghten charismatic leadership effect to employee performance. On the other hand, job satisfaction weaken the effect of motivation to employee performance. Organizational culture moderated by job satisfaction does not have effect on employee performance.